Selection indices for identifying heat tolerant of maize (Zea mays) - Longmei, Ningthaipuilu; Gill, G.K.; Kumar, R.; Zaidi, Pervez H. (Indian Council of Agricultural Research, 2023)
Drought and heat stress have become the most prevailing problems for maize (Zea mays L.) crop production. Therefore, development of stress tolerance has become an essential goal in a breeding programme. Hence, an experiment was conducted at Punjab Agricultural University, Ludhiana, Punjab to identify heat tolerant DH lines in maize during spring season, 2016 and 2017. A total of 32 DH lines were evaluated under heat stress and non-stress conditions. Five stress tolerance indices such as Tolerance Index (TOL), Mean Productivity (MP), Geometric Mean Productivity (GMP), Stress Susceptibility Index (SSI) and Stress Tolerance Index (STI) were calculated based on grain yield under heat stress (Ys) and non-stress conditions (Yp). Grain yield under stress condition showed a negative significant association with TOL and SSI while positive significant correlation with MP, GMP and STI. Similarly, grain yield under non stress condition showed positive significant association with TOL, MP, GMP and STI. Based on two years data and using MP, GMP and STI, DH line DH_4_23 and DH_4_47 were found to be the most heat tolerant. These lines may be used as a potential source for heat stress tolerance and can be further used in heat stress tolerant breeding programme.